Desain dan Simulasi Kendali PID Kecepatan Motor Mesin Sentrifugasi - Rahmawati; Arief Mardiyanto; Siti Amra3; Muhammad Kamal; Jenne Syarif (Jurnal Serambi Engineering, 2024)
Centrifugal machines perform centrifugation by rapidly spinning materials using a motor. This study aims to identify the optimal control parameters (kp, ki, kd) for maintaining the stability of centrifugal machine operations using PID control. The transfer function of the centrifugation motor was obtained using the System Identification Tool (SIT) in Matlab. The transfer function was obtained by measuring several variations in the input and output of the centrifuge machine motor. The PID parameters were determined using the Ziegler-Nichols method, resulting in the following values: kp=18, kd=12, ki=6.3. The performance of the PID control system was tested and the results were as expected: overshoot = 9%, rise time = 3.87 seconds, and steady-state error = 2%. The system identification approach successfully determined the PID parameters and control performance to meet the desired motor requirements.